2021
DOI: 10.1108/qrfm-02-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative inquiry into the capital structure decisions of overconfident finance managers of family-owned businesses in India

Abstract: Purpose The purpose of this study is to understand the impact of the overconfidence of finance managers on the capital structure decisions of family-run businesses in the Indian scenario. Furthermore, this study aims to demonstrate that measurable managerial characteristics explain the capital structure decisions of managers. Design/methodology/approach The qualitative approach to research, which aims at understanding a given phenomenon among the experts, is followed. Semi-structured interviews are conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Each interview line was read, and detailed notes were prepared from the participant’s responses. In agreement with prior studies (Clark et al , 2022; Mahendru et al , 2022; Mundi et al , 2021), I categorized the codes better to understand the comparative financial behavior of TPs and CPs. The assigned codes and categories were shown to a senior colleague, and detailed discussions were held to ensure the clarity of analysis.…”
Section: Methodsmentioning
confidence: 65%
“…Each interview line was read, and detailed notes were prepared from the participant’s responses. In agreement with prior studies (Clark et al , 2022; Mahendru et al , 2022; Mundi et al , 2021), I categorized the codes better to understand the comparative financial behavior of TPs and CPs. The assigned codes and categories were shown to a senior colleague, and detailed discussions were held to ensure the clarity of analysis.…”
Section: Methodsmentioning
confidence: 65%
“…Fourth, existing literature does not incorporate the role of behavioral biases in the decision-making of management of funds under the purview of alternative investments. Existing literature provides evidence of the presence of biases among CEOs (Guenzel and Malmendier, 2020), finance managers (Mundi et al , 2021) and traders (Lee and Piqueira, 2019). We suggest investigating this question through the application of psychology and behavioral finance to alternative investments.…”
Section: Research Gaps and Directions For Future Researchmentioning
confidence: 99%
“…In the literature, the methodology and results of the Brusov-Filatova-Orekhova (BFO) theory are well known (for example, see references [16][17][18][19][20][21][22][23][24][25][26][27]). A number of papers (see, for example, [22][23][24]) have used the BFO theory in practical calculations.…”
Section: A Literature Review On the Development Of The Capital Cost A...mentioning
confidence: 99%
“…In [23], the influence of the overconfidence of finance managers on the capital structure decisions of family-run businesses in India was studied. It was shown that the capital struc-ture decisions of managers could be explained by measurable managerial characteristics.…”
Section: A Literature Review On the Development Of The Capital Cost A...mentioning
confidence: 99%